Chapter The ARPA FVG support to oil spill emergency response in the gulf of Trieste (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Along shipping lanes the density of the ships is very high resulting, in a non-negligible probability of pollutant release in the sea. So, it is extremely important to react promptly to an oil spill emergency, to avoid that the pollutant spreads. This work describes services that are ready to use in case of oil spill. Services integrate weather and marine forecasts into a numerical model simulating the dispersion of the oil slick. Details are presented, together with applications during simulated ship collisions or accidental released along the routes. The focus is on the Adriatic area.